Language in an interior life: The Loser and Glenn Gould - Robalo, Cristina (Rivista Italiana di Filosofia del Linguaggio, 2012)
This paper aims to reflect on Thomas Bernhard's novel The Loser, Glenn Gould and his performance of the Goldberg Variations, and blind drawing The experience and understanding of the creative process in Thomas Bernhard's work and in Glenn Gould are similar while remaining unique and individual; as in blind drawing, there is a process of sharing, through experience and understanding, among those who propose to undertake blind drawing exercises. However, the route that is drawn/inscribed on the paper is always a journey that concerns each individual alone. In the reflection undertaken, literature, music and drawing (my area of knowledge) establish a union that stems from an aesthetic used to analyse the creative process. Walter Benjamin and Gaston Bachelard support and uphold the aim of engendering an image situated between the work and the creator: the medium – transparency and opacity. The conception of art, in this case music, as the main element in The Loser gives rise to a plot involving characters, writer and performer, which, in its reality/unreality, unites the work and the creator – the veil that reveals the dual participation of fear and desire: art as language